Kourdoulas, Panayiotis - (:unkn) unknown (My University, 2026)
Panagiotis Kourdoulas has received a bachelor degree from the Department of Agricultural Sciences, Biotechnology & Food Science at Cyprus University of Technology, majoring in Plant Sciences (2008-2012). He continued his post-graduate studies in the same University in the field of Plant Biotechnology. His scientific interests include the quality evaluation of fleshy fruits with the use of physiological and biochemical and phytochemical approaches. To date Panos is co-author of 3 publications in referrred journals. He is currently working on a private company (Tsakistos) dealing with citrus and pomegranate and olive production.